Implications of growth rates and compensatory growth on puberty attainment in Nellore heifers - Miszura, A. A. (2021)
This study investigated the effects of growth rates and compensatory growth on puberty attainment in Nellore heifers. Nellore heifers (n = 120), weaned at 8 ± 0.75 mo of age, were blocked by sire and BW (180 ± 8.6 kg) and assigned randomly to receive 1 of 4 treatments over a 10-mo period. Treatments included ad libitum feeding (high gain, HG), feed intake to gain 0.6 kg/d (medium gain, MG), restricted feeding (0.2 kg/d) for 4 mo followed by ad libitum feeding for 6 mo (compensatory gain, CG), and alternating periods of ad libitum and restricted feeding for 2 mo each throughout the trial (alternated CG, ACG). Puberty was assessed weekly by transrectal ultrasonography. Blood samples were collected at 8, 11, and 18 mo of age and at puberty to determine circulating concentrations of leptin. At 18 mo of age, nonpubertal heifers were treated with a puberty induction protocol using an intravaginal progestin device. There was no treatment effect (P = 0.17) on the percentage of heifers pubertal by 18 mo of age (HG: 66, MG: 40, CG: 58, and ACG: 52%), BW at puberty, and age at puberty. However, HG heifers had higher ADG (P < 0.01), dry matter intake (P < 0.01), and leptin concentrations (P = 0.03) than heifers from other groups. The response to the puberty induction protocol was similar (P = 0.90) among treatments. Regarding sire effects (genetic effects), there was an effect (P = 0.03) on the percentage of heifers pubertal by 18 mo of age and a tendency (P = 0.07) of sire effect in response to the puberty induction protocol. Compensatory growth appears to be an effective managerial approach to decrease feeding costs and stimulate puberty in Nellore heifers.